(untitled) (Eurasian Journal of Ecology, 2016)
It is established that useful wild bees and wasps almost everywhere in South-eastern Kazakhstan suffered the considerable shortage of the places for nesting. The method of breeding of aculeate Hymenoptera with help of artificial nests not only in economic aims but also for conservation and enriching of their biodiversity in anthropogenic biotopes is offered. For making of nests the wooden bars, boards, boughs and branches of trees, where tubular cavities were drilled, and also dry stems of raspberry, reed, burdock, horse sorrel, hemp, chicory, different umbellate, topinambour, wormwood and other plants were used. Recommendations for breeding of wasps and solitary bees with help of artificial nests are worked out. Fabrication and placement of artificial nests is one of the accessible forms of involvement of public at large in the global problem of biodiversity conservation.